Abitare le resistenze. Il caso del quartiere Aurora a Torino tra immigrazione, lotta per la casa e gentrification - Sossich, Erasmo (Antropologia Pubblica, 2024)
This contribution investigates the action of the Spazio Popolare Neruda, a housing squat where dozens of families of different nationalities cohabit, in the neighborhood of Valdocco. Turin’s district of Aurora (where Valdocco is located) is close to the historical center and focus of rapid gentrification processes; it is also characterized by the historical presence of a high percentage of foreigners and by rapid social change.The article proceeds by analyzing the difficult post-industrial transition of the neighborhood, mainly characterized by the loss of industrial working class identity and by international immigration. The attention is then brought on the use of space made by residents, highlighting how the spatial proximity between the different inhabitants corresponds to a deep social distance.We then proceed with the analysis of the strategies and the practices adopted by the inhabitants of Neruda and the housing rights movement, aimed on the one hand at opposing everyday life segregation through mutual and cultural activities, and on the other hand at claiming housing rights and the right to the city.To conclude the article brings forward the opposition to the urban regeneration policies, deemed as responsible for a selective inclusion and exclusionary operation, however promoted by the combination of rhetorics of participatory governance and urban decorum.